-20u+12.03=-18.5u-15.27-5.4u

Simple and best practice solution for -20u+12.03=-18.5u-15.27-5.4u equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -20u+12.03=-18.5u-15.27-5.4u equation:


Simplifying
-20u + 12.03 = -18.5u + -15.27 + -5.4u

Reorder the terms:
12.03 + -20u = -18.5u + -15.27 + -5.4u

Reorder the terms:
12.03 + -20u = -15.27 + -18.5u + -5.4u

Combine like terms: -18.5u + -5.4u = -23.9u
12.03 + -20u = -15.27 + -23.9u

Solving
12.03 + -20u = -15.27 + -23.9u

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '23.9u' to each side of the equation.
12.03 + -20u + 23.9u = -15.27 + -23.9u + 23.9u

Combine like terms: -20u + 23.9u = 3.9u
12.03 + 3.9u = -15.27 + -23.9u + 23.9u

Combine like terms: -23.9u + 23.9u = 0.0
12.03 + 3.9u = -15.27 + 0.0
12.03 + 3.9u = -15.27

Add '-12.03' to each side of the equation.
12.03 + -12.03 + 3.9u = -15.27 + -12.03

Combine like terms: 12.03 + -12.03 = 0.00
0.00 + 3.9u = -15.27 + -12.03
3.9u = -15.27 + -12.03

Combine like terms: -15.27 + -12.03 = -27.3
3.9u = -27.3

Divide each side by '3.9'.
u = -7

Simplifying
u = -7

See similar equations:

| 3x+2(x+5)=4(x+6) | | 10(6t+1)-15=t-(t+4) | | 121-5x=13x+19 | | x^3+2x^2-x=o | | -13v-16.08=1.76+9.22-10.8v | | 6x-4y+11=0 | | 6r^2-7r-5=5 | | -(15r+15)=3(-4r+1) | | -3(-4x+2)=5(x-3) | | 3(x+3)+3x=4(x+6)+1 | | x^4+72x-20=0 | | 8x+12=68 | | 2+g=14 | | -4(-2+5)=6(x-3) | | 9n-(2n-3)=10 | | 44+55= | | 4y-10+y+54=8y+50-6y | | x-2y=21 | | -(10x+1)+3=-9+6x | | -4x+2=8x-26 | | 5x-7+x=4+5x | | 6x-6=4x+2 | | 20-n=10-2 | | 3x+x+1.5x+180=455 | | (n-1)(5n-2)=0 | | 3x+x+1.5+180=455 | | 5x-12=4x-14 | | -9x^2-48x+15= | | 3x-5=4+2x+8 | | w^2+w=0 | | w=7h+80 | | 5(y-2)=-2(12-9)+y |

Equations solver categories